2004
DOI: 10.1002/hyp.1373
|View full text |Cite
|
Sign up to set email alerts
|

Estimating evapotranspiration from a reed bed using the Bowen ratio energy balance method

Abstract: Abstract:An increase in demand for water for agricultural and domestic use, combined with new legislation regarding the water needs of natural habitats, has led to an increased requirement for accurate calculations of hydrological fluxes through wetlands. Evapotranspiration is one of the most important but least well understood fluxes in wetland hydrology. Research has been carried out on Stodmarsh National Nature Reserve in Kent, UK, a Ramsar site containing the largest reed beds in southern England. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 27 publications
3
41
2
2
Order By: Relevance
“…The results of the daily evapotranspiration totals in summer, obtained using the eddy covariance methods, are quite similar to the results obtained for marshland areas in Europe, Siberia and Canada. Daily totals at a level of 2-3.5 mm were obtained during a few weeks of summer measurements in the wetlands overgrown by reeds (Reed Belt) (Peacock and Hess 2004), or also in wet meadows (Gasca-Tucker et al 2007) in southern England. Also in northern Germany (Herbst and Kappen 1999) and Canada (Lafleur et al 2005), evapotranspiration in summer from the surfaces of marshlands where the dominant vegetation is reed is characterized by daily totals at a level of 2-4 mm·d −1…”
Section: Evapotranspirationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the daily evapotranspiration totals in summer, obtained using the eddy covariance methods, are quite similar to the results obtained for marshland areas in Europe, Siberia and Canada. Daily totals at a level of 2-3.5 mm were obtained during a few weeks of summer measurements in the wetlands overgrown by reeds (Reed Belt) (Peacock and Hess 2004), or also in wet meadows (Gasca-Tucker et al 2007) in southern England. Also in northern Germany (Herbst and Kappen 1999) and Canada (Lafleur et al 2005), evapotranspiration in summer from the surfaces of marshlands where the dominant vegetation is reed is characterized by daily totals at a level of 2-4 mm·d −1…”
Section: Evapotranspirationmentioning
confidence: 99%
“…For example, in the direct measurement of evapotranspiration lysimeters (and more specifically, a set of several lysimeters) are used, enabling simultaneous evaluation of evaporation loss of water from individual bog formations and from an open water surface (Abtew and Obeysekera 1995;Abtew and Melesse 2013). In the direct measurements, microclimatic methods based on the Bowen ratio are also used (Burba et al 1999;Campbell and Williamson 1997;Kellner 2001;Peacock and Hess 2004), as well as methods based on the measurements of fluctuations of groundwater levels (Gerla 1992;Lafleur et al 2005;Grygoruk et al 2011;Grygoruk et al 2014;Mazur et al 2014). Furthermore, the results of evaporation evaluation, obtained using the Penman equation, the Penman-Monteith equation or the water balance are also widely presented (Wessel and Rouse 1994;Campbell and Williamson 1997;Souch et al 1998;Jacobs et al 2002;Gasca-Tucker et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…AET measurements were performed using the Bowen ratio energy balance The assumptions made when using the Bowen ratio technique (Peacock and Hess 2004) are: (1) Turbulent transfer coefficients for heat and water vapor are identical. A recent study found that the similarity theory applied in all atmospheric stability situations, thus confirmed earlier work such as Businger et al (1971) and Crawford (1965).…”
Section: Methodsmentioning
confidence: 99%
“…The crop coefficient (K c ) is the ratio of AET to the reference crop evapotranspiration (ET 0 ) calculated by the FAO Penman-Monteith equation (Peacock andHess 2004, Watanabe et al 2004). ET 0 is defined as the evapotranspiration of a surface similar to a short green grass with an assumed crop height of 0.12 m, a fixed surface resistance of 70 m/s and an albedo of 0.23 (Allen et al 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation